Preliminary Empirical Validation of the “Basic Needs Satisfaction in Sport Scale” With a Sample of Spanish Athletes - De Francisco, Cristina; Parra, Francisco J.; Arce, Constantino; Vílchez, M. D. Pilar (Frontiers in Psychology, 2018)
Abstract The theory of self-determination establishes the existence of three basic psychological needs (autonomy, competence and relationship). If these needs are satisfied, optimal personal well-being will be achieved. The Basic Needs Satisfactions in Sport Scale (BNSSS) is a measurement developed to evaluate these needs within the sporting context. The BNSSS measures the satisfaction of the three basic psychological needs through 20 items distributed in five dimensions: autonomy-choice, autonomy-volition, autonomy-perceived locus of internal causality, competence and relationship. The purpose of this study is to validate a Spanish version of the BNSSS. The sample were 441 team athletes with a mean age of 17.46 (SD = 3.59), which 46.5% were men and the remaining percentage (53.5%) were women. After a standardized data collection, confirmatory factor analysis and invariance analyses were performed, as well as composite reliability. The obtained version showed a good overall fit of the model and values of composite reliability higher to .70. Therefore a useful tool for assessing basic psychological needs in team sports was obtained.